2014
DOI: 10.1007/s11427-014-4646-x
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional effect of Wnt signaling antagonist DKK1 on the modulation of anthrax toxin uptake

Abstract: LRP6, a co-receptor for the morphogen Wnt, aids endocytosis of anthrax complexes. Here we report that Dickkopf1 (DKK1) protein, a secreted LRP6 ligand and antagonist, is also a modulator of anthrax toxin sensitivity. shRNA-mediated gene silencing or TALEN-mediated gene knockout of DKK1 reduced sensitivity of cells to PA-dependent hybrid toxins. However, unlike the solely inhibitory effect on Wnt signaling, the effects of DKK1 overexpression on anthrax toxicity were bidirectional, depending on its endogenous ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 61 publications
(88 reference statements)
1
12
0
Order By: Relevance
“…DKK1 is a secretory protein that was first verified to have regulatory effect on the development of embryonic head in xenopus laevis. Subsequently, DKK1 was supposed to have regulatory effect on Wnt/β-catenin signal pathway in human (16). Later, it is confirmed in numerous studies that DKK1 plays an important role in the genesis and metastasis mechanisms of tumor, and it is verified in some tumors to have value in predicting prognosis (17).…”
Section: Discussionmentioning
confidence: 92%
“…DKK1 is a secretory protein that was first verified to have regulatory effect on the development of embryonic head in xenopus laevis. Subsequently, DKK1 was supposed to have regulatory effect on Wnt/β-catenin signal pathway in human (16). Later, it is confirmed in numerous studies that DKK1 plays an important role in the genesis and metastasis mechanisms of tumor, and it is verified in some tumors to have value in predicting prognosis (17).…”
Section: Discussionmentioning
confidence: 92%
“…When distributed on the cell membrane, it also has an adhesion function but can additionally participate in autophagy, promote cell apoptosis, and recruit transferrin [43]. Adhesion, as the first step of bacterial infection, is of great significance to the invasive ability of bacteria and the effective use of toxins [44]. The results showed that the degree of expression in the biofilm state is higher than that in a planktonic state.…”
Section: Discussionmentioning
confidence: 99%
“…In Wnt signaling pathway, DKK1 can form ternary complex with LRP6 and Kremen2, another membrane protein, for internalization 12 13 . We have recently reported that DKK1 plays an important role in the internalization and lethality of anthrax toxin through the ternary structure of LRP6-DKK1-Kremen2 14 . However, it is still technically challenging to investigate the function of secreted protein in real time without toilsome protein production and purification processes.…”
mentioning
confidence: 99%